(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
This article presents part of a state-of-the-art research on scenic characterization in Brazil, conducted between 2011 and 2021. The study, which is bibliographic and documentary in nature, sought to map academic productions in the field of Performing Arts that address costume design, makeup, and theatrical characterization in their interface with the performer’s body. The investigation covered databases such as SCIELO, BDTD, CAPES, specialized journals, and the GT Traje de Cena e Traje de Folguedo (Stage Costume and Costume Design Working Group) of the Fashion Colloquium. Twenty-five works were identified, including dissertations, theses, and articles, which reveal advances and gaps in the consolidation of characterization as a field of research, highlighting the importance of integrating body, costume, and dramaturgy in creative processes.